مشكلات الطلاب في قسم تعليم اللغة العربية في مهارة الكلام - Cut Keumalawati (Yayasan Madinah Al-Aziziyah, 2023)
This study investigates the challenges faced by students in the Arabic Language Education Department at STIT Al-Hilal Sigli, in developing speaking skills, as well as the strategies employed by lecturers to address these challenges. Using a descriptive-analytical method, data were collected through observation, interviews, questionnaires, and documentation. Findings reveal that students’ speaking difficulties stem from both internal and external factors. Internal factors include limited vocabulary mastery, insufficient practice, lack of confidence, fear of making mistakes, low motivation, and difficulty in sentence construction and idea generation. External factors involve the absence of a supportive language environment, limited opportunities for interaction, perceptions of Arabic as a difficult language, peer ridicule, time constraints, and insufficient learning media. To address these issues, lecturers encourage students to use Arabic actively in classroom interactions, integrate Arabic-based learning media, foster listening habits, create a language environment at least twice a week, and implement reward-and-punishment strategies.